Eco-friendly synthesis of Fe3O4 nanoparticles: Evaluation of their catalytic activity in methylene blue degradation by kinetic adsorption models - Ruíz-Baltazar, Álvaro de Jesús; Reyes-López, Simón Yobanny; Mondragón-Sánchez, María de Lourdes; Robles-Cortés, Anel Ivonne; Pérez, Ramiro (Results in physics, 2019)
In this work the green synthesis of Fe3O4 nanoparticles by cynara cardunculus leaf extract is presented. This green synthesis route offers a novel and eco-friendly alternative to obtaining of iron oxides nanoparticles. Functional nanoparticles with potential catalytic applications, particularly for water remediation containing organic dyes were synthetized. The structural characterization of the Fe3O4 nanoparticles were carried out by scanning electron microscopy (SEM), X-ray diffraction, techniques. Calculation to obtaining the crystallite size by Williamson –Hall method were performed. Additionally, Raman spectroscopy support the Fe3O4 characterization. Posteriorly, the Fe3O4 nanoparticles were evaluated on the methylene blue degradation. Kinetic adsorption models were employed to establish the behavior during the methylene blue degradation process. Pseudo first order, Pseudo second order, Intraparticle diffusion and Elovich Models were calculated based on the experimental data obtained. Calculations as the correlation factor indicates the best linear fit between the theoretical models and the experimental data obtained during the blue methylene degradation.